Long-Baseline Neutrino Oscillation Experiments - G. J. Feldman; J. Hartnell; T. Kobayashi (Advances in High Energy Physics)
A review of accelerator long-baseline neutrino oscillation experiments is provided, including all experiments performed to date and the projected sensitivity of those currently in progress. Accelerator experiments have played a crucial role in the confirmation of the neutrino oscillation phenomenon and in precision measurements of the parameters. With a fixed baseline and detectors providing good energy resolution, precise measurements of the ratio of distance/energy (L/E) on the scale of individual events have been made and the expected oscillatory pattern resolved. Evidence for electron neutrino appearance has recently been obtained, opening a door for determining the CP violating phase as well as resolving the mass hierarchy and the octant of θ23; some of the last unknown parameters of the standard model extended to include neutrino mass.